Arctic warming and your weather: public belief in the connection. (26th July 2013) - Hamilton, Lawrence C.; Lemcke‐Stampone, Mary
ABSTRACT Will Arctic warming affect mid‐latitude weather? Many researchers think so, and have addressed this question through scientific articles and news media. Much of the public accepts such a connection as well. Across three New Hampshire surveys with more than 1500 interviews, 60% of respondents say they think future Arctic warming would have major effects on their weather. Arctic/weather responses changed little after Superstorm Sandy brushed the region, but exhibit consistently strong partisan divisions that grow wider with education. Belief in an Arctic/weather connection also varies, in a nonlinear pattern, with the temperature anomaly around day of interview. Interviewed on unseasonably warm or cool days, respondents are more likely to think that Arctic warming would have major effects on their weather. This unscientific response seems to mirror the scientific discussion about extremes.